Genetic Optimization of Neural Networks for Person Recognition Based on the Iris - Patricia Melin; Victor Herrera; Danniela Romero; Fevrier Valdez; Oscar Castillo (Universitas Ahmad Dahlan, 2012)
This paper describes the application of modular neural network architectures for person recognition using the human iris image as a biometric measure. The iris database was obtained from the Institute of Automation of the Academy of Sciences China (CASIA). We show simulation results with the modular neural network approach, its optimization using genetic algorithms, and the integration with different methods, such as: the gating network method, type-1 fuzzy integration and optimized fuzzy integration using genetic algorithms. Simulation results show a good identification rate using fuzzy integrators and the best structure found by the genetic algorithm.